Family Protection in Lebanon: Between a Flawed Structure and a Needed Reform - Efrem, Micheline (Technium Social Sciences Journal, 2026)
Social exclusion is today one of the major social issues of our societies, whether developed or developing. In Lebanon, family protection, regulated by a few scattered texts, have so far largely been the work of charitable associations and religious institutions, in the absence of a social plan adopted by the State in this domain. A reform project for family social protection could evolve as a “Social State” that recognizes and guarantees social rights for everyone and for all.